Mobile phone usage pattern and its health effects among medical students in north Karnataka: an observational study - Sinha, Sweta; Patil, Manjula S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The mobile phone is viewed as an important communication tool and is an integral part of the human society in the present era. Medical students use smart phones for note taking, imaging, web browsing, text books, question banks etc. Excessive mobile phone use has been found to be associated with health problems such as impaired concentration, headache, fatigue, thermal sensations in and around ear, stress, sleep disturbances and frustration. Objective was to explore the mobile phone usage pattern and its health effects among medical students. Methods: An observational study was conducted among medical students of Belagavi. The calculated sample size was 277 after taking the prevalence of mobile phone usage pattern of 76.4%. The questionnaire consists of socio-demographic characteristics, pattern of mobile phone usage like mode of use, time of maximum use etc. and the health effect variables like headache, restlessness, neck pain, painful fingers etc. Statistical analysis was done using MS-Excel 2007 and SPSS v 22, proportion and chi-square test was applied and p<0.05 was considered significant. Results: 98.19% were using smart phone and 85.56% were having single phone. Maximum were using for 2-4 years (42.60%). Internet was used for academic purpose in 89.89%. Majority of them experienced eyes symptoms (55.23%) followed by sleep deprivation (46.21%) and headache (42.60%). Conclusions: Even though mobile phone has positive role in our daily lives, its overuse leads to negative impact on health, sleep, and academic performance of students.